A review of coal mine saline mine water treatment and utilization technologies - Weidong MAO; Zhongquan GUO; Yuan FU; Jiuli YANG; Xufeng XU; Yantao WU; Zhipeng TANG; Jun ZHANG; Dongfeng CUI; Junzhao ZHU (Meitan kexue jishu)
China’s coal production is dominated by underground mining. With increasing mining depth, there is an observed rise in the proportion of saline mine water emissions. Saline mine water is mine water with a total salt content exceeding 1 000 mg/L. Based on the distinct ionic composition, China’s saline mine water is categorized into five types: chloride type, sulfate type, carbonate type, chloride-sulfate type, and composite type. The predominant types are chloride type, sulfate type, and chloride-sulfate type. In light of the problem of mine water with a total salt content that exceeds the prescribed standard, the state and local governments have introduced the requirement of salt discharge limitation, and have conducted research and practical application in treating saline mine water. The development history and research status of salt mine water treatment technology internationally are described, and the advantages and disadvantages of the pretreatment process, membrane concentration process, and evaporation crystallization process are analyzed, as well as the applicable conditions. The whole process treatment technology for salt-containing mine water involves a combination of pretreatment, multi-stage membrane concentration, and salt crystallization. The discussion encompasses the technical characteristics, scope of application, and status of high-efficiency reverse osmosis (HERO) and moderate step-by-step synergistic treatment technology (SPMS2) in the context of differing membrane concentration pre-treatment processes. Similarly, the technical characteristics, scope of application, and status of evaporation salt crystallization and nanofiltration salt crystallization technologies are discussed concerning different salt crystallization processes. Concerning the challenges currently faced by membrane concentration and evaporation crystallization technology, and the future development direction, the following proposals are put forward: the ongoing advancement of high-efficiency short-flow membrane concentration and low-carbon evaporation crystallization processing technology and equipment; the sustained investigation of the conversion of low-value by-product salts and the extraction of high-value components; actively explore the joint treatment mode of low-grade heat source, geothermal or photovoltaic power and salt-containing mine water; proactively investigate the regional centralized treatment mode of salt-containing mine water; and explore the technical, policy and economic feasibility of off-grid new energy applications, and study naturally enhanced evaporation and concentration technologies.